1998
DOI: 10.1038/nsb0698-432
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the dimer a initiation complex of HIV-1 genomic RNA

Abstract: Retroviral genomes must dimerize to be fully infectious. Dimerization is directed by a unique RNA hairpin structure with a palindrome in its loop: hairpins of two strands first associate transiently through their loops, and then refold to a more stable, linear duplex. The structure of the initial, kissing-loop dimer from HIV-1, solved using 2D NMR, is bent and metastable, its interface being formed not only by standard basepairing between palindromes, but also by a distinctive pattern of interstrand stacking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
159
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 26 publications
14
159
1
1
Order By: Relevance
“…Indeed, many structural studies relied on a flash cooling procedure to ensure the formation of the hairpin form. This was the case for several crystallographic studies (see Introduction) as well as for an NMR study of the DIS(Lai) kissing complex (44). More importantly, most of the crystal studies performed for describing a hairpin structure finally resulted in the description of a duplex structure, which clearly shows that the cooling procedure was unimportant.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, many structural studies relied on a flash cooling procedure to ensure the formation of the hairpin form. This was the case for several crystallographic studies (see Introduction) as well as for an NMR study of the DIS(Lai) kissing complex (44). More importantly, most of the crystal studies performed for describing a hairpin structure finally resulted in the description of a duplex structure, which clearly shows that the cooling procedure was unimportant.…”
Section: Discussionmentioning
confidence: 96%
“…In these complexes, base complementarity exists not only between the intermolecular hairpin loops, but also between the stem regions. In the case of the dimer initiation complex of the HIV-genomic RNA, a metastable intermolecular kissing interaction culminates in a linear duplex isoform stabilized by intermolecular base pairing (20,44). A kissing interaction also initiates the binding of the antisense RNA CopA to its target, CopT, but the outcome of this interaction is an unusual four-way junction defined by the predicted base stacking arrangements of intramolecular helices and newly formed intermolecular helices (19,45).…”
Section: Discussionmentioning
confidence: 99%
“…NMR data recorded on weakly aligned samples allowed us to obtain a structural model in solution of an RNA-RNA kissing complex with higher accuracy and precision than previously reported kissing complex solution structures (14,20,(22)(23)(24)(25)(26). This structural study revealed the key atomic interactions responsible for the stabilizing role of the GA base pair at the loop-closing position of kissing complexes.…”
mentioning
confidence: 88%
“…First, the number of paired loop residues can vary from two up to seven (22,23,35). In addition, some of the kissing complexes possess nonpaired bases (22,24,25,(47)(48)(49). For example, the crystal structures of the HIV-1 MAL and LAI kissing complexes (49), the anticodon-anticodon interaction in tRNA Asp (47), and a loop-loop interaction in 23S rRNA (48) show coaxial alignment of the two opposite stems due to flanking residues on the 5Ј side.…”
Section: Curvature Of Kissing Complexes Lacking Unpaired Residuesmentioning
confidence: 99%